Review Paper on Marketing Management - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
This paper aims to explain the central marketing and marketing management principle using the means of existing studies. Occasionally, however, business students are found to restrict the marketing term and limit it to advertisement or promotional activities. Nevertheless, this paper contributes to the enrichment of student awareness and attempts to reduce misunderstanding among young students. Accordingly, the analysis is compiled using systematic literature review through research papers, books, official web sources and some interviews with senior professors in the marketing management discipline. The current study therefore attempted to illustrate the marketing term and showed that marketing is not limited to promotional activities. Notwithstanding this, it is a full strategic mechanism that creates value for the consumers and strengthens their long-term relationships. While promoting the product through distinct advertising media, marketing management is an essential element of the process. In addition, the present study provides marketing students with a basis for understanding the basics of marketing theory.